Tourism Carrying Capacity (TCC) of Tongkonan Lempe Tourism Attraction, North Toraja Regency - Yabarmase, Antonius Christian Sine Marannu; Wicaksono, Agus Dwi; Dinanti, Dian; Munenge, Sizyoongo (Journal of Regional and Rural Studies, 2023)
Tongkonan Lempe is one of tourist attraction in Lolai Tourist Area in Kapala Pitu Subdistrict, North Toraja Regency. Based on North Toraja Regional Spatial Plan 2012-2023, Kapala Pitu Subdistrict was set as a landslide-prone area. However, in the Lolai tourist area, there was a large-scaling land clearing for tourist objects without regard to environmental impact. The purpose of this study is to determine the Ecological Carrying Capacity and Economic Carrying Capacity of Tongkonan Lempe Tourism Object. The method used in this research is the Cifuentes Method to determine ecological carrying capacity which consists of Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), Management Carrying Capacity (MCC), and Effective Carrying Capacity (ECC). Meanwhile, to determine Economic Carrying Capacity use Cost Benefit Analysis. Existing tourist visits have exceeded the value of the environmental carrying capacity. The Tongkonan Lempe tourist attraction can only accommodate a maximum of 31 tourists per day, while the average number of visits in 2022 is expected to be 122 visitors per day.According to the cost-benefit analysis, the Tongkonan Lempe tourist attraction's management will have to spend IDR 50,596,000 to preserve environmental quality with the current number of visitors of 122. If the number of visitors is lowered to an environmentally ideal level of 31, the net economic profit value is IDR 17,236,000 because the environmental conditions are still maintained. Several recommendations can be made based on several literature sources to raise the ecological carrying capacity including: replanting by adding types of vegetation to increase the value of the flora diversity correction factor, increasing the number of officers to improve services, especially during holidays, and limiting the number of tourists.